Understanding the implications of digitisation and automation in the context of Industry 4.0: A triangulation approach and elements of a research agenda for the construction industry - Oesterreich, Thuy Duong; Teuteberg, Frank (Computers in industry, 2016)
•An industry specific definition of the Industry 4.0 concept for construction has been derived based on a content analysis.•A systematic literature review is conducted to explore the state of the art of Industry 4.0 in the construction industry.•A practical view has been added by performing a multiple case study analysis.•A PESTEL framework has been illustrated to present the implications of Industry 4.0 for the construction industry.•Recommendations for further research are provided within a research agenda. In recent years, Industry 4.0 has been introduced as a popular term to describe the trend towards digitisation and automation of the manufacturing environment. Despite its potential benefits in terms of improvements in productivity and quality, this concept has not gained much attention in the construction industry. This development is founded in the fact that the far-reaching implications of the increasingly digitised and automated manufacturing environment are still widely unknown. Against this backdrop, the primary objective of this paper is to explore the state of the art as well as the state of practice of Industry 4.0 relating technologies in the construction industry by pointing out the political, economic, social, technological, environmental and legal implications of its adoption. In this context, we present the results of our triangulation approach, which consists of a comprehensive systematic literature review and case study research, by illustrating a PESTEL framework and a value chain model. Additionally, we provide recommendations for further research within a research agenda.